2021
DOI: 10.1002/smll.202103501
|View full text |Cite
|
Sign up to set email alerts
|

Ion Irradiation Inducing Oxygen Vacancy‐Rich NiO/NiFe2O4 Heterostructure for Enhanced Electrocatalytic Water Splitting

Abstract: Oxygen evolution reaction (OER) is an obstacle to the electrocatalytic water splitting due to its unique four‐proton‐and‐electron‐transfer reaction process. Many methods, such as engineering heterostructure and introducing oxygen vacancy, have been used to improve the catalytic performance of electrocatalysts for OER. Herein, the above two kinds of regulation are simultaneously realized in a catalyst by using unique ion irradiation technology. A nanosheet structured NiO/NiFe2O4 heterostructure with rich oxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(45 citation statements)
references
References 36 publications
2
39
1
3
Order By: Relevance
“…47 Forming a heterostructure, as a type of interfacial structure, is a favorable strategy to enhance the catalytic performance of materials, which not only overcomes the inherent disadvantages of each material but also generates new properties due to interfacial effects. 48–52 In particular, heterogeneous nanointerfaces with a built-in electric field have demonstrated outstanding electrocatalytic activities because they can boost the interfacial charge transfer during electrocatalytic processes and effectively influence the adsorption of the corresponding reactants and intermediates. 53–55 Therefore, the construction of Cu-based materials/MnO 2 heterostructures with well-designed built-in electric fields is advantageous for enhancing the activity of electrochemical nitrate reduction to ammonia.…”
Section: Introductionmentioning
confidence: 99%
“…47 Forming a heterostructure, as a type of interfacial structure, is a favorable strategy to enhance the catalytic performance of materials, which not only overcomes the inherent disadvantages of each material but also generates new properties due to interfacial effects. 48–52 In particular, heterogeneous nanointerfaces with a built-in electric field have demonstrated outstanding electrocatalytic activities because they can boost the interfacial charge transfer during electrocatalytic processes and effectively influence the adsorption of the corresponding reactants and intermediates. 53–55 Therefore, the construction of Cu-based materials/MnO 2 heterostructures with well-designed built-in electric fields is advantageous for enhancing the activity of electrochemical nitrate reduction to ammonia.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, this catalysis mechanism of constructing an Ru/FeCoP heterointerface to drive dual active site overcomes the problems of the high cost and low water-decomposition efficiency of noble metal-based catalysts. 48,49…”
Section: Resultsmentioning
confidence: 99%
“…When NiCo 2 O 4 is gradually formed during annealing, a large number of O v will be generated. Many studies have shown that O v has been proven to exert favorable roles in promoting HER ( Zhang et al, 2018b ; Li et al, 2021b ; Lu et al, 2021 ) and OER ( Liu et al, 2019 ; Xiao et al, 2020 ; Zhong et al, 2021 ) activity in alkaline conditions, mainly because the O v lowers the coordination numbers of active metal ions, and thus modifies their electronic structures and further tunes the adsorption strength of HER and OER intermediates (*H for HER, and *OH, *O and *OOH for OER) on them and the O v also can decrease the energy barriers during HER or OER processes ( Zhu et al, 2020b ; Badreldin et al, 2021 ; Wu et al, 2021 ). Together plus the effects of the smaller sizes, NiCo 2 O 4 -2KCl with the more O v can expose more active sites on its surface and achieves the higher EASAs ( Figure 6A ) as compared with NiCo 2 O 4 .…”
Section: Resultsmentioning
confidence: 99%